DO KNOWLEDGE AND AWARENESS AFFECT THE IMPLEMENTATION OF GREEN PRACTICES? THE PERSPECTIVES OF HIGHER EDUCATION STUDENTS IN MALAYSIA - Aziz, Roslizawati Che; Hashim, Nik Alif Amri Nik; Yusoff, Abdullah Muhamed; Awang, Zaimatul; Simpong, Derweanna Bah; Omar, Raja Norliana Raja; Othman, Nur Azimah (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to investigate the association among factors that have influenced the implementation of green practice activities among students in higher education.Self-administered questionnaires were applied to collect data from students in higher education institutions. About 457 questionnaires were distributed to the students through a random sampling technique.The findings of the study have shown that the independent variables, which are knowledge and awareness, have positive relationships in the implementation of green practice activities among students in higher education.This current study is beneficial for the management of universities to gain more understanding of how to attract students towards implementing green practices. Furthermore, this study’s outcomes supply useful data towards increasing the knowledge and awareness of green practices at higher education institutions. Therefore, the results of the work can be utilised as a referral point for any succeeding study in improving green practices.